Power Relation of a Sexual Harassment Victim in Penyalin Cahaya: A Critical Discourse Analysis - Ammar, Faris Faishal; Triyono, Sulis; Margana, Margana (Humaniora, 2023)
This study aims to analyze the struggle of sexual harassment victims depicted in the film entitled Penyalin Cahaya. This study uses Fairclough’s critical discourse analysis (CDA) model and the Outrage Management model (Scott & Martin, 2006) to examine the verbal and visual aspects of the film. The dimensions that are analyzed include the text, the discourse practice, and sociocultural practice. The key dialogues and scenes are extracted by selecting and retrieving excerpt of dialogues and scenes which depict conflict and power imbalances between the victims and the perpetrators. The results show that power imbalance and its manifestation between them can be found by observing the dialogue and the scenes. It demonstrates that there are several ways through which the abusers exercise their power over the victims. It also highlights the attempts by the victims to fight against sexual harassment, which is often ignored. Furthermore, the sociocultural state of Indonesian society, especially regarding patriarchal culture and power struggles over women, became the main driver that led to the production of this film. The significance of this study is that it can provide insight into the positions, emotions, and obstacles faced by sexual harassment victims in Indonesia, as depicted in the film.